Russian Bancassurance Perspectives: From Path Dependence to Ecosystem - Yu. S. Evlakhova (Финансы: теория и практика, 2022)
The aim of the study is to identify the future of Russian bancassurance in the “digital” world based on the formation of a reasonable opinion on its prospects within the framework of path dependence and the ecosystem approach. The relevance of the article is determined by the significance of bancassurance for the development of the insurance sector and the Russian financial market as a whole. The author uses methods such as analysis and synthesis, analogy, induction, descriptive analysis, matrix construction, clustering using graphs, and index method. The study is based on the works of domestic and foreign authors, data from the Bank of Russia on the state of the banking sector of the Russian Federation and key indicators of the insurers; reports of the rating agency “RA Expert” on bancassurance; data of Professional Analysis Systems of Markets and Companies Interfax. Based on the results of quantitative analysis, the author concludes that the key factor determining the development of Russian bancassurance within the framework of path dependence is the role of banks as recipients of cash flows. The author shows that the digital transformation of bancassurance is mainly associated with the digitalization of intermediary relations between the bank, individual client and insurance company. To quantify the level of such transformation, the author proposes indices of digitalization of bancassurance. The author shows that bancassurance can be successfully built into ecosystems due to its peculiarities. However, the conditions for the development of ecosystems in the Russian market can lead to the dissolution of bancassurance in ecosystems and the loss of its significance for the development of the Russian financial market. The presented conclusions are to be discussed taking into account the study of new issues in this problem area, including a study of the mergers and acquisitions market to analyse changes in the ownership structure of banks and insurance companies; a study of corporate bancassurance; broader analysis of quantitative values of bancassurance due to new data; analysis of ecosystem development in the Russian financial market in order to move from predictive judgments to a discussion of real situations.